Modeling depth of drainage ditches in forested peatlands in Finland - Hökkä, Hannu; Stenberg, Leena; Laurén, Ari (Institute of Forestry, LAMMC, 2020)
Drainage ditches have been dug in peatlands and paludified forests in order to enhance forest growth in an area of 4.7 M ha in Finland. Because of peat subsidence, bank erosion, sedimentation, and ingrowth of vegetation ditches deteriorate with time. In this study the shallowing of ditch depth over time was investigated on the basis of country-wide peatland inventory data measured repeatedly up to four times. Mixed linear models were constructed separately for original ditches and maintained ditches (cleaned once or twice). After 20 years the ditches were 20-30 cm shallower than right after the digging. Time since digging was the most important variable explaining the shallowing for both original and maintained ditches. Other variables explaining the ditch shallowing were the digging method (excavator, plow), ditch bed slope, location, and peat layer thickness. The average development of maintained and original excavator ditches was very similar. The results can be used in assessing decision making concerning ditch cleaning.
Keywords: forest drainage; ditch depth; ditch network maintenance; modeling; peatlands